(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
A comparative study of production /catch in open water fish habitats was conducted both inside and outside the embankment of Meghna Dhonagoda Irrigation Project (MDIP). Very low production was observed in the khal/canal (24.32 kg /ha and 26.45 kg /ha), inundated paddy field/ floodplain (1.99 kg / ha and 2.24kg / ha) in inside the embankment in 2003-2004 and 2004-2005, where the production/Catch per unit area was higher in khal (531.56 kg /ha and 528.77kg /ha), floodplain (38.18 kg /ha and 33.84 kg /ha) in outside during the same years. Beside these, the production/catch was recorded in irrigation canal (13.90 kg /ha and 21.94 kg /ha) in inside the embankment of both the years. On the other hand, the catch was recorded in Meghna river (137.87 kg /ha and 96.27 kg /ha) and in Dhonagoda river (124 kg /ha and 85.92 kg /ha) in outside the embankment of both the years respectively. The production was little bit higher in inside open water habitats in 2004-2005, escaped fishes from the ponds were also caught in the inside open water habitats in 2004-2005 due to the over flooding of ponds caused by excess rainfall in September 2004. In both the years, the highest production of inside habitats was in khal, followed by irrigation canal and inundated paddy field/ floodplain. In case of outside habitats, the highest production was in khal, followed by Meghna river, Dhonagodariver and floodplain during both the years of study. Monthly estimated catch regarding the production of the equal sample area of the same habitats between the two zones are statistically significant (p<0.05) in both 2003-2004 and 2004-2005. Asiat. Soc. Bangladesh, Sci. 43(2): 245-257, December 2017